Respostas
respondido por:
5
Oi.
x[2x-(3-x)]-3(x²-1)=0
x[2x-3+x]-3x²+3=0
x[3x-3]-3x²+3=0
3x²-3x-3x²+3=0
-3x=-3
x=1
x[2x-(3-x)]-3(x²-1)=0
x[2x-3+x]-3x²+3=0
x[3x-3]-3x²+3=0
3x²-3x-3x²+3=0
-3x=-3
x=1
respondido por:
5
x[2x-(3-x)]-3(x²-1)=0
x[2x-3+x]-3x²+3=0
x[3x-3]-3x²+3=0
3x²-3x-3x²+3=0
-3x=-3 (o -3 não pode ficar negativo no primeiro membro então ×(-1) )
3x=3
X=3/3
X=1
Espero ter lhe ajudado! :-)
x[2x-3+x]-3x²+3=0
x[3x-3]-3x²+3=0
3x²-3x-3x²+3=0
-3x=-3 (o -3 não pode ficar negativo no primeiro membro então ×(-1) )
3x=3
X=3/3
X=1
Espero ter lhe ajudado! :-)
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás